E-government: from actors to interrelations. (16th November 2010) - Foteinou, Georgia-Barbara; Pavlidis, Georgios
E-government, as an interdisciplinary area of research, exhibits some special difficulties related to its sociotechnical character. This paper adopts a systems approach of e-government, to offer a unified framework of analysis. This approach offers a deeper understanding of e-government as an interactive, open multi-level, sociotechnical system, which is embedded to a hyper-system and entails many other subsystems that result to a high degree of complexity. At first, e-government is defined as a system whose constituent parts are entities and relationships. Then, some system characteristics are specified and its social and technological aspects are taken into account.